Pengaruh Store Image, Store Athmosphere, dan Store Theatric terhadap Impulse Buying dengan Emosi Positif sebagai Variabel Mediasi pada Toko Princess Cosmetic Banjarmasin. - Regina Maharani Nurlie; Raden Roro Yulianti Prihatiningrum; Emy Rahmawati (JURNAL BISNIS DAN PEMBANGUNAN, 2021)
This study aims to examine and analyze the influence of Store Image, Store Athmosphere, and Store Theatric on Impulse Buying mediated by Positive Emotions at Banjarmasin Cosmetics Shop.This research method uses quantitative research methods. Using a purposive sampling technique by collecting data through the distribution of questionnaires to consumers Banjarmasin Princess Cosmetics Shop who make purchases outside of planning, and at least 17 years old. The total sample in this study were 100 people. Furthermore, hypothesis testing uses SEM - PLS analysis. the results of the study prove that the 10 hypotheses tested were stated to be significant.Keywords: Store Image, Store Athmosphere, and Store Theatric, Impulse Buying, Positive Emotions